Moderasi dalam Pandangan Al-Qur’an dan Bible - Khairunnisa Khairunnisa; Indra Harahap; M. Ali Azmi Nasution (ANWARUL, 2023)
This thesis is entitled Dialogue of the Qur'an and the Bible About Religious Moderation, while the formulation of the problem is what is meant by the dialogue of the Qur'an and the Bible about religious moderation and what is the mechanism for the dialogue of the Qur'an and the Bible about religious moderation. This study aims: 1) to find out the Al-Qur'an dialogue about religious moderation, 2) to analyze the Biblical dialogue about religious moderation, and 3) to provide materials or references for students of the Study of Religions on the dialogues of the Qur'an and the Bible about moderation in religion. The approach used is normative theology, which is an attempt to understand religion using the framework of divinity which departs from a belief that the empirical form of a religion is considered the most correct compared to the others. While the theory is inductive, a thought that departs from specific rules (things or events) to determine general laws (rules). The findings from the results of this study are dialogues which are written works, presented in the form of conversations between two or more figures in a straightforward manner, also carried out through questions and answers about an issue as desired. The results of this study indicate that in Islam and Christianity with the way of dialogue teaches about how to understand each other and be tolerant in religious moderation. So that between the two religions, especially the Qur'an and the Bible, they understand each other that the dialogue in question serves to convey a message to other people that aims to touch the basic values of religion.